Electric field induced, superhydrophobic to superhydrophilic switching in multiwalled carbon nanotube papers - Kakade, Bhalchandra A.; Mehta, Rutvik; Durge, Apurva; Kulkarni, Sneha; Pillai, Vijayamohanan (Nano Letters, 2008)
Superhydrophobic multiwalled carbon nanotube bucky paper, fabricated after ozonolysis, shows fascinating electrowetting behavior, which could be remarkably tuned by changing key solution variables like the ionic strength, the nature of the electrolyte, and the pH of the water droplet. More significantly, the droplet behavior can be reversibly switched between superhydrophobic, Cassie-Baxter state to hydrophilic, Wenzel state by the application of an electric field, especially below a threshold value.